Explicitation strategy in the translation of 'Rihlah Ibn Battutah' into English - Syed Abdullah, Syed Nurulakla; Abd Rahman, Mohd Zaki; Mohamad, Ab Halim; Ismail, Muhd Zulkifli (2015)
In translation, the utterances delivered in the form of implicit meaning in Arabic are not necessarily appropriate to retain that form in English. This results in a reversal, with the form of the implicit meaning being translated into the explicit meaning form. This study aims to identify the forms of implicit meaning in the book ‘Rihlah Ibn Battutah’ and to explore the influence of culture on this translation and the strategies used by the translator to deal with the difficulties of translating the implicit meaning. This study is a qualitative study using case study and textual analysis methods based on the approach proposed by Klaudy and Károly (2005), and Pym (2005). The data analysis was carried out using ATLAS.ti software. The results of this study not only show that explication in translation is driven by cultural factors in general but also that it is significantly influenced by religious influences, Arabic Rhetorical Sciences (Balāghah), lexicogrammatical and pragmatic factors, communicative preferences and the politeness of the target language itself. This study will hopefully spark interest and a deeper focus on explicitation strategy in the field of translation.